PENGARUH ENTREPRENEURIAL AGILITY DAN ENTREPRENEURIAL TRAITS TERHADAP DIGITAL ENTREPRENEURSHIP INTENTION MAHASISWA - Puspa Tarti Saridiningrat; Edi Afriza Fitriana; Sri Hardianti Sartika (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the effect of entrepreneurial agility and entrepreneurial traits on digital entrepreneurship intention partially and simultaneously. The research method used is the survey method. The sampling technique used is probability sampling with the two-stage cluster random sampling method. The results show that: 1) Entrepreneurial Agility has a positive and significant effect on Digital Entrepreneurship Intention with a significance value of 0.000 <0.05. 2) Entrepreneurial Traits have a positive and significant effect on Digital Entrepreneurship Intention with a significance value of 0.011 <0.05. 3) Entrepreneurial Agility and Entrepreneurial Traits have a simultaneous effect on Digital Entrepreneurship Intention as evidenced by Fcount 110.796> Ftable 3.05 with a significance value of 0.000 <0.05.